Development of piperazine-based hydroxamic acid inhibitors against falcilysin, an essential malarial protease. Issue 10 (1st June 2018) - Chance, Jeffrey P.; Fejzic, Hannah; Hernandez, Obiel; Istvan, Eva S.; Andaya, Armann; Maslov, Nikolay; Aispuro, Ruby; Crisanto, Teodulo; Nguyen, Huyen; Vidal, Brian; Serrano, Whitney; Kuwahara, Bradley; et al.
Graphical abstract: Highlights: Piperazine-based hydroxamic acids are the first reported inhibitors of falcilysin. Lead compound has potent activity against falcilysin and cultured P. falciparum. Falcilysin may be a promising point for therapeutic intervention. Abstract: The human parasite Plasmodium falciparum kills an estimated 445, 000 people a year, with the most fatalities occurring in African children. Previous studies identified falcilysin (FLN) as a malarial metalloprotease essential for parasite development in the human host. Despite its essentiality, the biological roles of this protease are not well understood. Here we describe the optimization of a piperazine-based hydroxamic acid scaffold to develop the first reported inhibitors of FLN. Inhibitors were tested against cultured parasites, and parasiticidal activity correlated with potency against FLN. This suggests these compounds kill P. falciparum by blocking FLN, and that FLN is a druggable target. These compounds represent an important step towards validating FLN as a therapeutic target and towards the development of chemical tools to investigate the function of this protease.